2002
DOI: 10.1073/pnas.072531099
|View full text |Cite
|
Sign up to set email alerts
|

Algal blooms reduce the uptake of toxic methylmercury in freshwater food webs

Abstract: Mercury accumulation in fish is a global public health concern, because fish are the primary source of toxic methylmercury to humans. Fish from all lakes do not pose the same level of risk to consumers. One of the most intriguing patterns is that potentially dangerous mercury concentrations can be found in fish from clear, oligotrophic lakes whereas fish from greener, eutrophic lakes often carry less mercury. In this study, we experimentally tested the hypothesis that increasing algal biomass reduces mercury a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
282
5

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 373 publications
(316 citation statements)
references
References 32 publications
29
282
5
Order By: Relevance
“…However, the methylmercury concentration in phytoplankton is the result of both MeHg uptake rate and phytoplankton growth. Uptake, which is partially governed by MeHg concentration in water (Mason et al 1996;Pickhardt and Fisher, 2007), will result in various MeHg concentration in plankton depending the rate of building cellular material; indeed a high primary production induces a biomass dilution phenomenon (Pickhardt et al, 2002). Joiris et al (1995) observed a significant negative correlation between Hg concentration and particulate organic carbon concentration in the particulate matter of the European Arctic Seas.…”
Section: Geographical Differences In Hg Concentration In the Red Mullmentioning
confidence: 99%
“…However, the methylmercury concentration in phytoplankton is the result of both MeHg uptake rate and phytoplankton growth. Uptake, which is partially governed by MeHg concentration in water (Mason et al 1996;Pickhardt and Fisher, 2007), will result in various MeHg concentration in plankton depending the rate of building cellular material; indeed a high primary production induces a biomass dilution phenomenon (Pickhardt et al, 2002). Joiris et al (1995) observed a significant negative correlation between Hg concentration and particulate organic carbon concentration in the particulate matter of the European Arctic Seas.…”
Section: Geographical Differences In Hg Concentration In the Red Mullmentioning
confidence: 99%
“…This can also be associated to an increase in metabolic activity and growth dilution (Pastor et al, 1996). Growth dilution can be defined as biomass-specific concentration of pollutants diminishes by accumulation of new biomass (Pickhardt et al, 2002). Growth dilution was observed in other species, such as in the Northern pike (Esox lucius), for mercury contamination (Verta, 1990).…”
Section: Pcbs Contaminations Along P Flesus Different Age Groupsmentioning
confidence: 99%
“…There is strong empirical evidence that the density of phytoplankton blooms affects the bioaccumulation of metals by algae biomass and metals biomagnifications (Pickhardt et al, 2002). To further clarify the influence of phytoplankton driven processes on metal distribution, the annual dynamics of cellular bound metals were measured and compared to phytoplankton growth during September of 2009 to August of 2010 in Lake Taihu.…”
Section: Cyanobloom Bio-diluted Effects On Heavy Metals In Lake Taihumentioning
confidence: 99%